Palatal Fibroma - A Case-report (Journal of College of Medical Sciences-Nepal, 2016)
Fibroma is a benign tumor of fibrous connective tissue. Fibromas represent inflammatory state rather than neoplastic conditions, which  are mostly sessile or slightly pendunculated with a smooth contour, pale pink and are  firm in consistency, which commonly  occurs on gingiva, tongue, buccal mucosa and palate. Cinical, radiographic and histopathologic data combined with surgical findings are though essential, but it requires further studies to determine the exact nature of such fibromatous lesions. A multidisciplinary approach is needed in the management of ffibrtous lesions, so as to minimize its recurrence and to improve the quality of life, providing better  functioning and esthetics.JCMS Nepal. 2016;12(1):36-9.